A Collaborative Multimodal Pain Management Pathway Reduces Opiate Consumption After Total Hip and Knee Arthroplasty - Mahmoud Khellah, BS; Thomas Huff, MD; Kathryn Schabel, MD; Jessica Foerster, BS; Leah Esposito, MD; Megan Rushkin, MPH; Ryland Kagan, MD (Arthroplasty Today, 2025)
Background: A collaborative effort with pharmacy, nursing and surgeons developed a multimodal pain management protocol for total hip and knee arthroplasty. This investigation aims to evaluate the effectiveness in reducing opiate consumption. Methods: Retrospective cohort study comparing 455 total hip and knee arthroplasty patients. We compared the first 206 multimodal pain management protocol and 249 standard-of-care pathway patients from January 2017 to March 2020. Primary outcome was postoperative morphine milligram equivalents (MMEs) per 24 hours. Secondary outcomes included total MME at discharge and total MME in the first 6 weeks following discharge. Results: Postoperative MME per 24 hours was lower in the multimodal pain management protocol group 57.0 (30.5, 94.3) median (interquartile range), compared with the standard of care group 84.7 (50.4, 139.6), P < .001. MME prescribed at discharge was reduced in the multimodal pain management group 300 (224, 450) compared to the standard of care group 525 (400, 750), P < .001. MME prescribed 6 weeks following discharge was reduced in the multimodal pain management group 150 (0, 590.6) compared to the standard of care group 400 (0, 1050), P = .01. Additionally, the length of stay was reduced in the multimodal group, P = .01, with similar postoperative pain scores across groups. Conclusions: Our collaborative multimodal pain management pathway reduced opiate consumption for patients undergoing total hip and knee arthroplasty with a reduction in LOS, no difference in pain scores and was effective for patients with various levels of opiate requirements. Level of Evidence: Level III Therapeutic Study: retrospective comparative study